2006
DOI: 10.1176/jnp.18.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Functions in Young Patients With Essential Tremor: A Case Comparison Study

Abstract: Essential tremor (ET) is classified as a pure motor system disease. It has been previously reported that impairments in cognitive functions can be associated with ET. The authors assessed cognitive functions in a relatively young patient group with ET and comparison subjects. Correlations between tremor severity and regional cerebral blood flow (rCBF) and neuropsychological test performances of ET patients and comparison subjects were investigated. Sixteen patients with ET and 16 comparison subjects were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 33 publications
8
57
0
5
Order By: Relevance
“…34 The overactivation of the cingulum and cerebellum during working memory trials in an fMRI study 33 may represent compensation for volume loss and loss of WM integrity of these areas observed in our study. We observed significant impairment of the visuospatial functions in ETCI, an observation similar to that reported by Sahin et al 3 Daniels et al 35 reported relative expansion of GM volume bilaterally in the region of the temporal parietal junction in patients with ET and attributed this to adaptive reorganization for compromised visuospatial functioning. In the present study, visuospatial dysfunction was correlated with diffusion measures of the right parieto-occipital lobe.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…34 The overactivation of the cingulum and cerebellum during working memory trials in an fMRI study 33 may represent compensation for volume loss and loss of WM integrity of these areas observed in our study. We observed significant impairment of the visuospatial functions in ETCI, an observation similar to that reported by Sahin et al 3 Daniels et al 35 reported relative expansion of GM volume bilaterally in the region of the temporal parietal junction in patients with ET and attributed this to adaptive reorganization for compromised visuospatial functioning. In the present study, visuospatial dysfunction was correlated with diffusion measures of the right parieto-occipital lobe.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have shown cognitive impairment, especially executive-visuospatial dysfunction and attention deficits, in patients with ET. 3,4 Voxel-based morphometry studies in ET have found volume reductions in the cerebellum and cerebrum (frontal lobe, insula, and cingulum). 5,6 While voxel-based morphometry analysis is useful for demonstrating regional GM changes, DTI provides information about the microstructural organization of WM.…”
mentioning
confidence: 99%
“…Studies on this subject showed cognitive impairment with affected visuospatial abilities, verbal memory, executive functions, verbal fluency, naming and working memory in ET (12,33,34,35,36). Moreover, in a limited number of studies conducted with young patients, this condition has been proved to be present even at early stages (6,13). In our study, we also found that visuospatial abilities and delayed recall functions were significantly impaired compared with the controls.…”
Section: Discussionsupporting
confidence: 70%
“…In several studies, findings suggesting cerebral-thalamocortical tract dysfunction were found in patients with ET. Mild cognitive impairment characterized by impairment of visuospatial functions, verbal memory, and executive functions has been shown in young patients (8,9,10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Association of ET with cognitive dysfunction Studies on cognition in ET have predominantly assessed two areas: the integrity of various neuropsychological abilities, particularly executive functioning [Kim et al 2009;Frisina et al 2009;Lombardi et al 2001;Higginson et al 2008;Gasparini et al 2001;Sahin et al 2006;Schwartz et al 1999;Passamonti et al 2011] and the extent to which patients with ET are at increased risk for mild cognitive impairment (MCI) or dementia [Benito-Leon et al 2006b;Bermejo-Pareja et al 2007;Thawani et al 2009]. …”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%